School Heads’ Perceptions of Coaching Practices in Primary Schools: A Pilot Study - Yusoff, Aziyah; Mohamad, Faridah; Yeop, Norhayati; Aziz Esa, Norhayati; Ramli, Normah; Mohammed Suberi, Nor Azlina (International Journal of Social Sciences Review, 2025)
Coaching has emerged as a transformative tool in educational leadership, providing school leaders with the strategies and resources crucial for sustainable and effective school improvement. This study explores how coaching practices impact school heads’ professional development, focusing on the influence of relevant content, effective delivery, and targeted instructional methods in fostering leadership growth. Specifically, it examines the role of coaching in developing school heads’ ability to address complex challenges with adaptability, thereby promoting a school culture that prioritizes continuous improvement. Based on a literature review and data from 27 purposively selected school heads from the Bera District Education Office in Pahang, the findings highlight that coaching is instrumental in enhancing leadership skills. Interestingly, demographic factors such as sex and years of experience were found to have no significant effect on coaching efficacy. This suggests that effective coaching practice relies less on tenure or background and more on targeted professional development, a growth mindset, and supportive institutional resources. The study underscores the importance of investing in structured coaching programs and organizational support to cultivate essential coaching skills, highlighting that coaching effectiveness is closely tied to continuous learning and committed engagement. These insights provide a compelling case for incorporating coaching as a core component of school leadership development, with the potential to elevate school performance and foster a positive impact on teachers.